Bone mineral density in elite adolescent female figure skaters - Prelack Kathy; Dwyer Johanna; Ziegler Paula; Kehayias Joseph J (Taylor & Francis Group, 2012)
Abstract Elite adolescent figure skaters must accommodate both the physical demands of competitive training and the accelerated rate of bone growth that is associated with adolescence, in this sport that emphasizes leanness. Although, these athletes apparently have sufficient osteogenic stimuli to mitigate the effects of possible low energy availability on bone health, the extent or magnitude of bone accrual also varies with training effects, which differ among skater disciplines. Purpose We studied differences in total and regional bone mineral density in 36 nationally ranked skaters among 3 skater disciplines: single, pairs, and dancers. Methods Bone mineral density (BMD) of the total body and its regions was measured by dual energy x-ray absorptiometry (DXA). Values for total body, spine, pelvis and leg were entered into a statistical mixed regression model to identify the effect of skater discipline on bone mineralization while controlling for energy, vitamin D, and calcium intake. Results The skaters had a mean body mass index of 19.8 ± 2.1 and % fat mass of 19.2 ± 5.8. After controlling for dietary intakes of energy, calcium, and vitamin D, there was a significant relationship between skater discipline and BMD (p = 0.002), with single skaters having greater BMD in the total body, legs, and pelvis than ice dancers (p < 0.001). Pair skaters had greater pelvic BMD than ice dancers (p = 0.001). Conclusions Single and pair skaters have greater BMD than ice dancers. The osteogenic effect of physical training is most apparent in single skaters, particularly in the bone loading sites of the leg and pelvis.